Biaccumulation and tolerance of heavy metals on the tropical earthworm, Allobophora sp. after exposed to contaminated soil from oil mine waste. (April 2018) - Suhendrayatna,; Darusman,; Raihannah,; Nurmala, D
Abstract: In this study, the impact of contaminated soil from oil mine waste on survival, behavior, tolerance, and bioaccumulation of heavy metals by the tropical earthworm, Allobophora sp. has been quantified. Earthworm was isolated from heavy metals-contaminated soil, cultured in laboratory condition, and exposed to contaminated soil from oil mine waste for a couple of months. The behavior and response of earthworms to contaminated soil was monitored for 28 days and evaluated by the response criteria was expressed in scale index (SI) referred to Langdon method. Resistance test of the earthworm (LC50 ) to heavy metals also conducted with variation soil concentrations of 100%, 50%, 25%, 12.5%, and 6.25%, and 0% (Control). Results showed that contaminated soil extremely affected to the earthworm live, especially length and their body weight. The Lethal Concentration 50% (LC50 ) of earthworm against contaminated soil was 19.05% (w/w). When exposed to contaminated soil, earthworm accumulated chromium, barium, and manganese at the concentration of 88; 92.2; and 280 mg/kg-DW, respectively. Based on these results, earthworm Allobophora sp. has potential to reduce heavy metals from contaminated soil in the field of bioremediation process.